Pemanfaatan Wordwall Game Fisika Terintegrasi Social Science Issue Untuk Meransang Berpikir Kritis Peserta didik - Defita Yusni; Hurriyah Hurriyah (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
The development of technology demands students to be able to integrate with it in their learning process. One digital medium that can assist students in learning is Wordwall. The aim of this research is to determine the utilization of the Wordwall website game in physics integrated with social science issues for students’ critical thinking abilities. This study employs a qualitative research approach with a literature review. The results indicate that the use of the Wordwall website is quite effective and efficient in enhancing students’ critical thinking skills, and the implication of social issues is the creation of student engagement.